ANALISIS MANAJEMEN SARANA DAN PRASARANA DI SEKOLAH DASAR NEGERI 048291 TIGAPANAH TAHUN PEMBELAJARAN 2024/2024 - Nadia Br Tarigan Nadia Br Tarigan; Antonius Remigius Abi; Darinda Sofia Tanjung; Regina Sipayung; Hambali (STAI Nusantara Kota Banda Aceh, 2026)
This study aims to analyze the management of facilities and infrastructure at SD Negeri 048291 Tigapanah in the 2024/2025 academic year. The focus of the study includes planning, procurement, maintenance, and evaluation of the utilization of school facilities and infrastructure, as well as the challenges faced in their management. This research employed a descriptive qualitative method, with data collected through interviews, observations, and documentation. The results indicate that the management of facilities and infrastructure at this school has been carried out gradually in accordance with learning needs, but it has not yet been fully optimized. Planning remains general and has not been entirely based on an in-depth needs analysis. The procurement of facilities and infrastructure follows the policies of the relevant education authorities, limiting the school’s ability to determine priorities. Maintenance is carried out periodically but lacks a systematic schedule. The evaluation of the utilization of facilities and infrastructure tends to be informal and is not yet based on measurable indicators. The main challenges faced include budget constraints, a lack of specialized technical personnel, and slow coordination processes with external parties. Recommendations include improving planning based on actual needs, establishing a structured maintenance schedule, and strengthening evaluation based on performance indicators for facilities and infrastructure. The findings of this study are expected to serve as a reference for primary schools in enhancing the effectiveness of facilities and infrastructure management to support quality learning processes.